2018
DOI: 10.1186/s40249-018-0466-8
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodic diapause in a subtropical population of Aedes albopictus in Guangzhou, China: optimized field-laboratory-based study and statistical models for comprehensive characterization

Abstract: BackgroundAedes albopictus is among the 100 most invasive species worldwide and poses a major risk to public health. Photoperiodic diapause provides a crucial ecological basis for the adaptation of this species to adverse environments. Ae. albopictus is the vital vector transmitting dengue virus in Guangzhou, but its diapause activities herein remain obscure.MethodsIn the laboratory, yeast powder and food slurry were compared for a proper diapause determination method, and the critical photoperiod (CPP) was te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…albopictus uses diapause at the egg stage to survive the low temperatures in winter and delay reproduction until favorable climatic conditions arrive. As a key environmental signal, the shortening of days will cause females to lay diapause-programmed eggs (halted development, reduced metabolism, and increased resistance) [46]. It is therefore likely that climatic conditions, at the end and beginning of diapause, might also have played a role in the phenotypic differentiation observed in adults in our study.…”
Section: Discussionmentioning
confidence: 94%
“…albopictus uses diapause at the egg stage to survive the low temperatures in winter and delay reproduction until favorable climatic conditions arrive. As a key environmental signal, the shortening of days will cause females to lay diapause-programmed eggs (halted development, reduced metabolism, and increased resistance) [46]. It is therefore likely that climatic conditions, at the end and beginning of diapause, might also have played a role in the phenotypic differentiation observed in adults in our study.…”
Section: Discussionmentioning
confidence: 94%
“…The low egg-hatching rate in the winter might be attributable to the overwintering of Ae. albopictus eggs or potential diapause [45,46]. Xia et al found that eggs collected from the field in Guangzhou may enter diapause when the photoperiod was about 12 h [45].…”
Section: Discussionmentioning
confidence: 99%
“…The most common source of Ae. albopictus incursions was southern China, where diapause has been observed in field populations [72]. Many other factors may also influence long-distance dispersal outcomes, such as differences in behaviour when boarding and travelling on vessels and the relative abundance of each species around airports and seaports.…”
Section: Sum Of Squaresmentioning
confidence: 99%